Aspects of Structural Design of Residential Buildings in Medan City, North Sumatra Province - Sitompul, Mizanuddin; Dary, Rhini Wulan; Tobing, Palghe; Nofriadi; Efrida, Rizki (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
Generally, residential buildings, especially low-rise ones in North Sumatra, are not well planned and built with poor supervision. In its planning, it often overrides the calculation of structural analysis. This residential building is known to have many failures during earthquakes. The research team is interested in studying the important elements in the design and construction of residential buildings, focusing on very crucial structural aspects. By considering these aspects comprehensively, it is hoped that the end result will be a sturdy, functional, and sustainable structural design of a residential building for its occupants.